Bringing Nitric Oxide to the Molybdenum World - Maia, Luísa (2023)
Molybdenum-containing enzymes of the xanthine oxidase (XO) family are well known to catalyse oxygen atom transfer reactions, with the great majority of the characterised enzymes catalysing the insertion of an oxygen atom into the substrate. Although some family members are known to catalyse the "reverse" reaction, the capability to abstract an oxygen atom from the substrate molecule is not generally recognised for these enzymes. Hence, it was with surprise and scepticism that the "molybdenum community" noticed the reports on the mammalian XO capability to catalyse the oxygen atom abstraction of nitrite to form nitric oxide (NO). The lack of precedent for a molybdenum- (or tungsten) containing nitrite reductase on the nitrogen biogeochemical cycle contributed also to the scepticism. It took several kinetic, spectroscopic and mechanistic studies on enzymes of the XO family and also of sulfite oxidase and DMSO reductase families to finally have wide recognition of the molybdoenzymes' ability to form NO from nitrite. Herein, integrated in a collection of "personal views" edited by Professor Ralf Mendel, is an overview of my personal journey on the XO and aldehyde oxidase-catalysed nitrite reduction to NO. The main research findings and the path followed to establish XO and AO as competent nitrite reductases are reviewed. The evidence suggesting that these enzymes are probable players of the mammalian NO metabolism is also discussed.